Identification of Food Diversity Factors to Overcome Stunting in Toddlers on the Musi River Suburbs, Palembang South Sumatra, Indonesia (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2022)
A diverse and balanced diet is one way to overcome stunting in toddlers. Without adequate food intake, toddlers will lack the nutrients to grow and develop properly. The purpose of this study was to identify the factors of various food choices in stunting toddlers on the outskirts of the Musi River, Palembang. This research is an observational study with a cross-sectional method conducted in two health centers representing the Musi River suburbs, namely Gandus Health Center and 11 Ilir Health Center. The subjects of this study were toddlers aged 6 months to 59 months, totaling 170 children under five who were calculated using the two-proportion hypothesis test formula and sampling through the purposive sampling technique. Data collection was carried out directly by interviews using a questionnaire. Chi-square test was used to analyze bivariate and multiple logistic regression test predictive model for multivariate analysis. Based on the results of the study, data obtained that there was a relationship between the mother's education (p = 0.000), number of family members (p = 0.017), food availability (p = 0.000), and eating patterns (0.005) with various foods. The results of multivariate analysis showed that maternal education and food availability had a significant relationship with food diversity. Mother's education has the greatest influence or is the most dominant risk factor for food diversity to overcome stunting in toddlers on the on the Musi River suburbs, Palembang. Mothers of toddlers should increase their knowledge about food diversity and provide food at home that does not have to be expensive but remains diverse and nutritionally balanced, in order to meet nutritional needs so that toddlers avoid stunting.